Positive plate, preparation method thereof and battery

By designing a double-layer positive electrode active material layer in the positive electrode sheet, the advantages of NCM and LMFP are used to optimize the electron and ion transmission efficiency, solve the problem of poor electron conduction/ion performance of LMFP, and improve the circulation performance and thermal of lithium-ion batteries. stability.

CN119208538APending Publication Date: 2024-12-27EVE POWER CO LTD

Patent Information

Application Number
CN202411259258.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The electron conduction/ion performance of lithium manganese iron phosphate (LMFP) cathode material has low electron conduction/ion performance, which affects its energy storage capacity and rate performance, limiting its large-scale application in high-performance lithium-ion batteries.

Method used

A positive electrode sheet with a double-layer positive electrode active material layer was designed. The first layer adopts LMFP+NCM mixed layer close to the current collector side, and the second layer adopts only LMFP away from the current collector side, which utilizes the high conductivity of NCM and the structural stability of LMFP. , optimize electron and ion transport efficiency, reduce polarization and thermal stability.

Benefits of technology

The conductivity and lithium ion effervescent efficiency of the LMFP-based positive electrode are improved, the polarization and thermal stability of the battery are reduced, the circulation performance and safety performance are improved, and the energy density and thermal stability of the battery are optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208538A_ABST
    Figure CN119208538A_ABST
Patent Text Reader

Abstract

The invention provides a positive plate, a preparation method thereof and a battery. The positive plate comprises a positive current collector, and a first positive active coating and a second positive active coating which are sequentially arranged on at least one side of the positive current collector, the first positive electrode active coating is close to one side of the positive electrode current collector, and the first positive electrode active coating comprises a first manganese iron lithium phosphate active material and a nickel-cobalt-manganese ternary active material; in the first positive electrode active coating, the mass ratio of the first lithium manganese iron phosphate active material to the nickel-cobalt-manganese ternary active material is (80-90): (8-15); the second positive electrode active coating is far away from one side of the positive electrode current collector, and the second positive electrode active coating comprises a second lithium manganese iron phosphate active material; the surface density rho1 of the first positive electrode active coating and the surface density rho2 of the second positive electrode active coating meet the following conditions: rho1 is greater than or equal to 240 g / m < 2 >, and rho2 is greater than or equal to 240 g / m < 2 >; and rho1-rho2 is less than or equal to 5g / m < 2 >. The positive plate has relatively high electron conduction and ion conduction performance, meanwhile, the polarization of the positive plate is effectively reduced, and the cycle performance and the thermal stability of the battery are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a positive electrode sheet and a preparation method thereof, and a battery. Background Art

[0002] Energy storage technology has developed rapidly in recent years, among which lithium-ion batteries are the most representative, and its mainstream representatives are lithium iron phosphate (LFP) and ternary (NCM) batteries. Lithium iron phosphate has the advantages of low cost, long cycle life and high safety. However, its energy density is low and its low-temperature performance is unsatisfactory; while ternary materials have high energy density and good rate performance, but the cost is also higher and there are certain safety risks.

[0003] Lithium manganese iron phosphate (LMFP) has a similar structure to lithium iron phosphate (LFP), both of which are olivine structures. It also has a higher voltage platform (4.2V), and can provide relatively higher energy density than LFP. In addition, LMFP has better low-temperature performance, and its capacity retention rate at -20°C is about 15% higher than LFP. Lithium manganese iron phosphate (LMFP) is developed on the basis of lithium iron phosphate (LFP) and lithium manganese phosphate (LMP). It combines the advantages of LFP and LMP, and thus has the characteristics of low cost, safety and stability, becoming a new type of lithium-ion battery positive electrode material with great market prospects. However, LMFP also has the inherent defects of olivine-type positive electrode materials, such as intrinsic electronic conductivity (10 -9 ~10 -10 S cm -1 ) and the lithium ion diffusion rate (10 -14 ~10 -16 cm 2 ·s -1 ) is low, which greatly affects its energy storage capacity and rate performance, and hinders its large-scale application in high-performance lithium-ion batteries.

[0004] In response to the poor electron / ion conductivity of LMFP, people have proposed a variety of modification methods based on theoretical research, mainly including surface coating, morphology control and ion doping. These modification methods have high requirements for material synthesis and are generally difficult to achieve large production, which has limited the large-scale application of LMFP to a certain extent.

[0005] Therefore, providing a modification method that can simply and effectively improve the performance of LMFP is of great practical significance for further promoting the large-scale application of LMFP in lithium batteries. Summary of the invention

[0006] In order to solve the problems and shortcomings existing in the prior art, the present invention provides a positive electrode sheet and a preparation method thereof, and a battery. The positive electrode sheet designed by the present invention contains a double-layer positive electrode active material layer. By controlling the positive electrode active material layer close to the current collector side to have a higher conductivity and the two layers of positive electrode active material layers to have very close surface densities, the designed positive electrode sheet has higher electron and ion conductivity, and at the same time effectively reduces the polarization of the positive electrode sheet, greatly improving the cycle performance and thermal stability of the battery.

[0007] According to a first aspect of the present invention, a positive electrode sheet is provided, comprising a positive electrode current collector and a first positive electrode active coating and a second positive electrode active coating sequentially arranged on at least one side of the positive electrode current collector; the first positive electrode active coating is close to the side of the positive electrode current collector, and the first positive electrode active coating comprises a first lithium iron manganese phosphate active material and a nickel-cobalt-manganese ternary active material; in the first positive electrode active coating, the mass ratio of the first lithium iron manganese phosphate active material to the nickel-cobalt-manganese ternary active material is 80-90:8-15; the second positive electrode active coating is away from the side of the positive electrode current collector, and the second positive electrode active coating comprises a second lithium iron manganese phosphate active material; the surface density ρ1 of the first positive electrode active coating and the surface density ρ2 of the second positive electrode active coating satisfy: ρ1≥240g / m 2 , ρ2≥240g / m 2 ; and |1-2|≤5g / m 2 .

[0008] For the modification of LMFP, compared with other modification methods, it is simpler, more convenient and more operable to directly use ready-made materials to physically mix and dope LMFP. Nickel-cobalt-manganese (NCM) ternary active materials are often used as modified LMFP materials because of their advantages such as high conductivity, high lithium ion diffusion performance, and high energy density. At present, most of the materials on the market are mixed with LMFP and NCM as active materials, and then the conductive agent and binder are used in combination according to the electrode formula ratio to make electrodes. For the pole pieces made by this method, the ion and electron transmission rates of the active materials on both sides close to the current collector and away from the current collector are inconsistent, which is easy to amplify the polarization phenomenon, resulting in unsatisfactory cycle life. A small part separates LMFP and NCM to make double-layer electrodes, but the pure NCM layer has poor thermal stability and safety risks.

[0009] This solution effectively improves the conductivity and lithium ion transfer efficiency of the LMFP-based positive electrode by designing a special double-layer positive electrode active material layer for the positive electrode sheet, thereby effectively reducing the battery DCR growth rate and improving the cycle performance of the LMFP-based positive electrode. Specifically, in the positive electrode sheet designed by the present invention, the first positive electrode active material layer (close to the positive electrode current collector) adopts a LMFP+NCM mixed layer, and the second positive electrode active material layer (away from the positive electrode current collector) only adopts an LMFP layer. With such a design, the first layer (lower layer) uses the high conductivity of NCM to improve the electron transfer rate on the current collector side, which can better cooperate with the ion transfer away from the current collector side, accelerate electron transfer, and thus can combine with ions in the electrolyte faster, improve electrochemical reaction activity, and then reduce polarization and improve cycle performance. The second layer (upper layer) only uses the LMFP layer. This is because LMFP has higher structural stability and higher electrolyte resistance. As an outer layer, it can play an effective interface barrier role for the inner LMFP+NCM layer, reducing the contact between the electrolyte and NCM, thereby reducing the side reactions on the positive electrode side, reducing the heat generated by the positive electrode, improving the thermal stability of the battery, and reducing the growth rate of the battery DCR, thereby further optimizing the battery's cycle performance and safety performance. At the same time, the LMFP outer layer can also play a certain role in blocking heat transfer and diffusion, further improving the thermal stability and safety performance of the battery.

[0010] Furthermore, the present invention further defines the surface density of the first positive electrode active material layer and the second positive electrode active material layer and the surface density difference. The purpose of controlling the two at the same time is, on the one hand, to control the surface density of the two positive electrode active material layers within a larger range, in order to ensure that the LMFP-based positive electrode sheet has a higher energy density, so as to fully improve the charge and discharge performance of the LMFP-based battery; on the other hand, to control the surface density difference of the two positive electrode active material layers to be less than a certain value, in order to ensure that the two active material layers have almost the same surface density, so that the electron and ion transmission efficiency of the two layers reaches a better balance, thereby effectively reducing the polarization of the battery during the charge and discharge cycle, reducing the growth of the battery DCR and optimizing the battery cycle performance.

[0011] In addition, the present invention further defines the mass ratio of the first lithium manganese iron phosphate active material to the nickel cobalt manganese ternary active material in the first positive electrode active material layer. Simultaneously controlling the layer density of the first and second positive electrode active materials, as well as the mass ratio of the first lithium manganese iron phosphate active material to the nickel cobalt manganese ternary active material, can be more conducive to ensuring the balance of lithium ion transmission, thereby making full use of the advantages of LMFP itself, such as long cycle life and high safety, reducing the degree of battery side reactions, reducing battery heat generation, thereby reducing battery polarization, and optimizing battery thermal stability and cycle performance.

[0012] Preferably, ρ1 and ρ2 satisfy: ρ1 = ρ2. Controlling the surface density of the first positive electrode active coating to be consistent with the surface density of the second positive electrode active coating can achieve a better balance in the electron and ion transmission efficiency of the two layers, further promote the synergistic effect, and further optimize the battery cycle performance.

[0013] Preferably, ρ1 and ρ2 satisfy: 240 g / m 2 ≤ρ1≤260g / m 2 , 240g / m 2 ≤ρ2≤260g / m 2 . Generally speaking, the greater the surface density of the positive electrode sheet, the higher the energy density of the battery. However, if the surface density of the positive electrode sheet is too high, the migration path of lithium ions becomes longer, the internal resistance of the battery is also larger, and congestion is likely to occur on the migration path of lithium ions, which will cause the lithium ions to be unable to be completely deintercalated in a short period of time, and finally lead to specific capacity loss. At the same time, it will also cause the operating temperature of the battery to increase, thereby affecting the life and safety of the battery. Therefore, controlling the surface density of the first positive electrode active coating and the second positive electrode active coating within a certain numerical range, that is, controlling the surface density of the positive electrode sheet within a specific numerical range, is conducive to taking into account the energy density of the battery as well as the cycle performance and safety performance.

[0014] Preferably, the thickness d1 of the first positive electrode active coating and the thickness d2 of the second positive electrode active coating satisfy: d1 ≥ 105 μm, d2 ≥ 105 μm, and |d1-d2| ≤ 3 μm. Generally speaking, the thicker the coating thickness of the positive electrode active material layer, the greater the capacity of the battery. However, excessive coating of the material will increase the internal resistance of the battery, affecting the output power and cycle life of the battery. Therefore, a balanced consideration is required in the selection of coating thickness. The present invention controls d1 and d2 within a certain numerical range, and controls the thickness difference between the two within a certain range, which is conducive to achieving optimal battery performance, thereby optimizing the cycle stability of the battery.

[0015] Preferably, the thickness D of the positive electrode sheet is ≥ 220 μm. Ensuring that the electrode sheet has a certain thickness is conducive to ensuring that the battery has a high energy density, and at the same time, both layers of positive electrode active material layers have a certain thickness, ensuring that the performance of the two layers of positive electrode active material layers is fully exerted, and optimizing battery performance.

[0016] Preferably, the thickness D of the positive electrode sheet satisfies: 220 μm ≤ D ≤ 230 μm. If the positive electrode sheet is too thick, the electron and ion transmission paths are longer, the sheet resistance increases, and it is not conducive to the cycle performance and thermal stability of the battery.

[0017] Preferably, the thickness of the positive electrode current collector is 10-15 μm.

[0018] Preferably, the positive electrode current collector includes aluminum foil. Preferably, the first positive electrode active coating also includes a first conductive agent and a first binder; the mass ratio of the first lithium manganese iron phosphate active material, the nickel cobalt manganese ternary active material, the first conductive agent, and the first binder is 80-90:8-15:1.2-1.8:1.5-3.

[0019] Preferably, the second positive electrode active coating further includes a second conductive agent and a second binder; the mass ratio of the second lithium manganese iron phosphate active material, the second conductive agent and the second binder is 92-98:1.2-1.8:1.5-3.

[0020] Preferably, the first conductive agent and the second conductive agent independently include conductive carbon black (SP) and carbon nanotubes (CNT).

[0021] Preferably, the first binder and the second binder independently include polyvinylidene fluoride (PVDF).

[0022] According to a second aspect of the present invention, a method for preparing the above-mentioned positive electrode sheet is provided, comprising the following steps: S1. preparing a lithium iron manganese phosphate positive electrode slurry using a second lithium iron manganese phosphate active material, a second conductive agent, and a second binder; preparing a lithium iron manganese phosphate mixed with nickel cobalt manganese ternary positive electrode slurry using a first slurry, a nickel cobalt manganese ternary active material, a first conductive agent, and a first binder; S2. controlling the viscosity difference between the lithium iron manganese phosphate positive electrode slurry and the lithium iron manganese phosphate mixed with nickel cobalt manganese ternary positive electrode slurry to be no more than 4000 mPa·s, and simultaneously coating the lithium iron manganese phosphate positive electrode slurry and the lithium iron manganese phosphate mixed with nickel cobalt manganese ternary positive electrode slurry on the positive electrode collector, drying, and obtaining a positive electrode sheet; the lithium iron manganese phosphate mixed with nickel cobalt manganese ternary positive electrode slurry is coated on the side close to the positive electrode collector, and the lithium iron manganese phosphate positive electrode slurry is coated on the side away from the positive electrode collector. Viscosity can be understood as the fluidity of the slurry. When the viscosity difference between the upper and lower layers (the second layer and the first layer) is too large, the surface density is not easy to control during the coating process, which can easily lead to a large difference in the surface density of the upper and lower layers, resulting in a large difference in the transmission efficiency of electrons and ions in the upper and lower layers, which in turn leads to increased polarization and decreased battery performance.

[0023] Preferably, in S1 or S2, the viscosity of the lithium iron manganese phosphate positive electrode slurry is controlled to be 8000-16000 mPa·s, and the viscosity of the lithium iron manganese phosphate mixed with nickel cobalt manganese ternary positive electrode slurry is controlled to be 8000-16000 mPa·s.

[0024] According to a third aspect of the present invention, there is provided a battery comprising the above-mentioned positive electrode sheet.

[0025] Preferably, the battery further comprises a negative electrode sheet, and the surface density of the negative electrode sheet is 100 to 105 g / m 2The thickness of the negative electrode sheet is 127-135 μm. Ensuring that the surface density and thickness of the negative electrode sheet are within the above range can better match the positive electrode sheet provided by the present invention, so that the battery has better cycle performance and thermal stability, and the DCR growth rate is lower.

[0026] Preferably, in the negative electrode sheet, the negative electrode active material layer comprises a negative electrode active material, a third conductive agent, and a third binder, and the mass ratio of the negative electrode active material, the third binder, and the third conductive agent is 92-97: 1.5-3: 1.5-3.5.

[0027] Preferably, the negative electrode active material includes graphite; the third conductive agent includes conductive carbon black (SP); and the third binder includes carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR).

[0028] Preferably, in the negative electrode sheet, the negative electrode current collector comprises copper foil.

[0029] In summary, the double-layer positive active material layer positive electrode sheet provided by the present invention can effectively improve the conductivity and ion conductivity of the LMFP material, reduce the growth of battery polarization and DCR, and thus effectively improve the cycle performance and thermal stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a schematic diagram of the positive electrode structure of one embodiment of the present invention. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.

[0032] Example 1

[0033] 1. Preparation of positive electrode

[0034] The positive electrode sheet of this embodiment is prepared according to the following steps:

[0035] S1. Using NMP (N-methylpyrrolidone) as solvent, LMFP (LiMn 0.6 Fe 0.4 PO4), SP, PVDF, and CNT are mixed and stirred in a mass ratio of 96.5:0.9:2:0.6 to obtain a LMFP positive electrode slurry, and the viscosity of the slurry outlet needs to be controlled at 8000-16000 mPa·s at 25°C;

[0036] At the same time, NMP is used as a solvent, and the obtained LMFP positive electrode slurry is mixed with NCM (NCM811), SP, PVDF, and CNT for mixing and stirring to obtain LMFP mixed with NCM positive electrode slurry, and the viscosity of the slurry discharge needs to be controlled at 8000-16000 mPa·s at 25°C; wherein, the amount of LMFP positive electrode slurry added is calculated based on the mass proportion of LMFP in the final first positive electrode active coating being 90%, and the mass proportion of NCM (NCM811) being 10%, and NCM (NCM811), SP, PVDF, and CNT are added in a mass ratio of 96.5:0.9:2:0.6.

[0037] S2. The above two positive electrode slurries are placed in a buffer tank respectively, and the viscosity difference between the two positive electrode slurries is controlled to be no more than 4000mPa·s. A double-layer coating die is used to uniformly coat the two positive electrode slurries on both sides of a 12μm aluminum foil (each side of the aluminum foil contains a first positive electrode active coating and a second positive electrode active coating), and the coating thickness of the two layers is controlled to be certain, wherein the LMFP mixed with NCM positive electrode slurry is coated on the side close to the aluminum foil, and the LMFP positive electrode slurry is coated on the side away from the aluminum foil, and dried at 90°C to obtain a positive electrode sheet; finally, in the positive electrode sheet prepared in this embodiment, the surface density of the first positive electrode active coating and the surface density of the second positive electrode active material layer are both 250g / m 2 , and the thickness of the first positive electrode active coating is 107 μm, and the thickness of the second positive electrode active coating is 107 μm.

[0038] refer to Figure 1 , which is a schematic diagram of the positive electrode sheet structure in this embodiment.

[0039] 2. Preparation of negative electrode and battery

[0040] (1) Preparation of negative electrode sheet

[0041] Using deionized water as solvent, artificial graphite, SP, CMC and SBR were mixed and stirred at a mass ratio of 95.5:2:0.5:2 to obtain a negative electrode slurry, and then the negative electrode slurry was coated on a copper foil of 8 μm and vacuum dried at 100°C to obtain a negative electrode sheet. The surface density of the negative electrode sheet prepared in this embodiment is 100 g / m 2 , thickness is 125μm.

[0042] (2) Preparation of batteries

[0043] The vacuum-dried positive and negative electrode sheets and separators are cut, die-cut, and striped, and then the electrolyte is injected under high temperature and negative pressure to assemble into a square aluminum shell battery; the electrolyte used is 1M LiPF6, 1:1.1 (mass ratio) of dimethyl carbonate (DMC) and ethylene carbonate (EC).

[0044] Example 2

[0045] 1. Preparation of positive electrode

[0046] In the process of preparing the positive electrode sheet of this embodiment, the difference from that of embodiment 1 is that the coating gasket control in the coating device is adjusted to adjust the gap between the gaskets to adjust the size of the surface density, so that in the positive electrode sheet finally prepared, the surface density of the first positive electrode active coating is 251.5 g / m 2 , and the surface density of the second positive electrode active material layer is 248.5 g / m 2 The remaining operations are consistent with those in Example 1.

[0047] 2. Preparation of negative electrode and battery

[0048] The preparation of the negative electrode sheet and the battery in this embodiment is consistent with that in Embodiment 1.

[0049] Example 3

[0050] 1. Preparation of positive electrode

[0051] In the process of preparing the positive electrode sheet of this embodiment, the difference from that of embodiment 1 is that the coating gasket control in the coating device is adjusted to adjust the gap between the gaskets to adjust the size of the surface density, so that in the finally prepared positive electrode sheet, the surface density of the first positive electrode active coating is 253.5 g / m 2 , and the surface density of the second positive electrode active material layer is 246.5 g / m 2 The remaining operations are consistent with those in Example 1.

[0052] 2. Preparation of negative electrode and battery

[0053] The preparation of the negative electrode sheet and the battery in this embodiment is consistent with that in Embodiment 1.

[0054] Example 4

[0055] 1. Preparation of positive electrode

[0056] In the process of preparing the positive electrode sheet of this embodiment, the difference from that of embodiment 1 is that the coating gasket control in the coating equipment is adjusted to adjust the gap between the gaskets to adjust the size of the surface density, so that in the positive electrode sheet finally prepared, the surface density of the first positive electrode active coating layer is 240 g / m 2 The remaining operations are consistent with those in Example 1.

[0057] 2. Preparation of negative electrode and battery

[0058] The preparation of the negative electrode sheet and the battery in this embodiment is consistent with that in Embodiment 1.

[0059] Example 5

[0060] 1. Preparation of positive electrode

[0061] In the process of preparing the positive electrode sheet of this embodiment, the difference from that of embodiment 1 is that the coating gasket control in the coating equipment is adjusted to adjust the gap between the gaskets to adjust the size of the surface density, so that in the positive electrode sheet finally prepared, the surface density of the first positive electrode active coating layer is 260 g / m 2 , and the thickness of the first positive electrode active coating layer and the second positive electrode active material layer are 107.5 μm and 107.5 μm respectively. The remaining operations are consistent with those in Example 1.

[0062] 2. Preparation of negative electrode and battery

[0063] The preparation of the negative electrode sheet and the battery in this embodiment is consistent with that in Embodiment 1.

[0064] Example 6

[0065] 1. Preparation of positive electrode

[0066] In the process of preparing the positive electrode sheet of this embodiment, the difference from that of embodiment 1 is that by adjusting the coating thickness of the LMFP mixed with NCM positive electrode slurry in S2, the thickness of the first positive electrode active coating layer in the final prepared positive electrode sheet is 103 μm, so that the thickness difference between the first and second positive electrode active material layers is 4 μm. The rest of the operations are the same as those of embodiment 1.

[0067] 2. Preparation of negative electrode and battery

[0068] The preparation of the negative electrode sheet and the battery in this embodiment is consistent with that in Embodiment 1.

[0069] 3. Preparation of negative electrode and battery

[0070] The preparation of the negative electrode sheet and the battery in this embodiment is consistent with that in Embodiment 1.

[0071] Example 7

[0072] 1. Preparation of positive electrode

[0073] In the process of preparing the positive electrode sheet of this embodiment, the difference from that of embodiment 1 is that by adjusting the coating thickness of the two positive electrode slurries in S2, the thickness of the first positive electrode active coating layer in the final prepared positive electrode sheet is 102 μm, the thickness of the second positive electrode active coating layer is 102 μm, and the total thickness of the positive electrode sheet is 214 μm. The remaining operations are consistent with embodiment 1.

[0074] 2. Preparation of negative electrode and battery

[0075] The preparation of the negative electrode sheet and the battery in this embodiment is consistent with that in Embodiment 1.

[0076] Example 8

[0077] 1. Preparation of positive electrode

[0078] In the process of preparing the positive electrode sheet of this embodiment, the difference from that of Example 1 is that by adjusting the coating thickness of the two positive electrode slurries in S2, the thickness of the first positive electrode active coating layer in the final positive electrode sheet is 112 μm, the thickness of the second positive electrode active coating layer is 112 μm, and the total thickness of the positive electrode sheet is 234 μm. The remaining operations are consistent with Example 1.

[0079] 2. Preparation of negative electrode and battery

[0080] The preparation of the negative electrode sheet and the battery in this embodiment is consistent with that in Embodiment 1.

[0081] Example 9

[0082] 1. Preparation of positive electrode

[0083] The positive electrode sheet in this embodiment is consistent with that in embodiment 1.

[0084] 2. Preparation of negative electrode and battery

[0085] In the preparation of the negative electrode sheet in this embodiment, the surface density of the prepared negative electrode sheet is controlled to be 107 g / m 2 .

[0086] The preparation of the battery in this example is consistent with that in Example 1.

[0087] Example 10

[0088] 1. Preparation of positive electrode

[0089] The positive electrode sheet in this embodiment is consistent with that in embodiment 1.

[0090] 2. Preparation of negative electrode and battery

[0091] In the preparation of the negative electrode sheet in this embodiment, the surface density of the prepared negative electrode sheet is controlled to be 98 g / m 2 .

[0092] The preparation of the battery in this example is consistent with that in Example 1.

[0093] Embodiment 11

[0094] 1. Preparation of positive electrode

[0095] The positive electrode sheet in this embodiment is consistent with that in embodiment 1.

[0096] 2. Preparation of negative electrode and battery

[0097] In preparing the negative electrode sheet in this embodiment, the thickness of the prepared negative electrode sheet is controlled to be 124 μm.

[0098] The preparation of the battery in this example is consistent with that in Example 1.

[0099] Comparative Example 1

[0100] 1. Preparation of positive electrode

[0101] In the process of preparing the positive electrode sheet of this comparative example, the difference from Example 1 is that by adjusting the coating gasket control in the coating equipment, the gap between the gaskets is adjusted to adjust the size of the surface density, so that in the positive electrode sheet finally prepared, the surface density of the first positive electrode active coating is 250.5g / m 2 , and the surface density of the second positive electrode active material layer is 241.5 g / m 2 The remaining operations are consistent with those in Example 1.

[0102] 2. Preparation of negative electrode and battery

[0103] The preparation of the negative electrode sheet and the battery in this comparative example is consistent with that in Example 1.

[0104] Comparative Example 2

[0105] 1. Preparation of positive electrode

[0106] In the process of preparing the positive electrode sheet of this comparative example, the difference from Example 1 is that by adjusting the coating gasket control in the coating equipment, the gap between the gaskets is adjusted to adjust the size of the surface density, so that in the positive electrode sheet finally prepared, the surface density of the first positive electrode active coating layer is 220 g / m 2 The remaining operations are consistent with those in Example 1.

[0107] 2. Preparation of negative electrode and battery

[0108] The preparation of the negative electrode sheet and the battery in this comparative example is consistent with that in Example 1.

[0109] Comparative Example 3

[0110] 1. Preparation of positive electrode

[0111] In the process of preparing the positive electrode sheet of this comparative example, the difference from Example 1 is that when coating the positive electrode slurry, both layers are coated with LMFP mixed with NCM positive electrode slurry, that is, the active materials of the first positive electrode active coating layer and the second positive electrode active coating layer are both LMFP+NCM. The rest of the operations are the same as Example 1.

[0112] 2. Preparation of negative electrode and battery

[0113] The preparation of the negative electrode sheet and the battery in this comparative example is consistent with that in Example 1.

[0114] Comparative Example 4

[0115] 1. Preparation of positive electrode

[0116] In the process of preparing the positive electrode sheet of this comparative example, the difference from Example 1 is that when coating the positive electrode slurry, the first layer (the side close to the aluminum foil) is coated with the LMFP positive electrode slurry, and the second layer (the side away from the aluminum foil) is coated with the NCM positive electrode slurry, that is, the active material layers of the first and second positive electrode active material layers are LMFP and NCM respectively; wherein, the preparation of the LMFP positive electrode slurry is consistent with that of Example 1; the preparation of the NCM positive electrode slurry is to use water as a solvent, mix and stir NCM (NCM811), SP, PVDF, and CNT in a mass ratio of 96.5:0.9:2:0.6 to obtain the NCM positive electrode slurry, and at the same time, the viscosity of the slurry discharge needs to be controlled at 8000-16000 mPa·s at 25°C. The rest of the operations are consistent with Example 1.

[0117] 2. Preparation of negative electrode and battery

[0118] The preparation of the negative electrode sheet and the battery in this comparative example is consistent with that in Example 1.

[0119] Comparative Example 5

[0120] 1. Preparation of positive electrode

[0121] In the process of preparing the positive electrode sheet of this comparative example, the difference from Example 1 is that the mass ratio of LMFP to NCM (NCM811) is adjusted when LMFP is mixed with NCM positive electrode slurry in S1, so that in the first positive electrode active material layer of the final positive electrode sheet, the mass proportion of the first lithium manganese iron phosphate active material is 90.5%, and the mass proportion of the nickel-cobalt-manganese ternary active material is 6%. The rest of the operations are the same as in Example 1.

[0122] 2. Preparation of negative electrode and battery

[0123] The preparation of the negative electrode sheet and the battery in this comparative example is consistent with that in Example 1.

[0124] Comparative Example 6

[0125] 1. Preparation of positive electrode

[0126] In the process of preparing the positive electrode sheet of this comparative example, the difference from Example 1 is that the mass ratio of LMFP to NCM (NCM811) is adjusted when LMFP is mixed with NCM positive electrode slurry in S1, so that in the first positive electrode active material layer of the final positive electrode sheet, the mass proportion of the first lithium manganese iron phosphate active material is 80%, and the mass proportion of the nickel cobalt manganese ternary active material is 16.5%. The rest of the operations are the same as in Example 1.

[0127] 2. Preparation of negative electrode and battery

[0128] The preparation of the negative electrode sheet and the battery in this comparative example is consistent with that in Example 1.

[0129] Test Case

[0130] 1. Experimental Construction Method

[0131] (1) DCIR test:

[0132] The batteries obtained from each embodiment and each comparative example were capacity calibrated at 1C at 25°C, and the SOC was adjusted to 50%. Then all the batteries were discharged at 1C for 30s at 50% SOC, and the discharge DCIR (DCR) was calculated, DCIR = (cut-off voltage after discharge - cut-off voltage before discharge) / current; and the DCR growth rate after 50 cycles was tested, DCIR growth rate = (50th cycle DCIR - initial DCIR) / initial DCIR. The test results are shown in Table 1.

[0133] (2) Cyclic performance test:

[0134] The batteries obtained in each embodiment and each comparative example were placed at 25° C. for 1 hour and then cycled at 1C / 1C with a charge and discharge voltage range of 2.5V–4.25V. The capacity retention rate of the batteries after 500 cycles was tested. The cycle test results are shown in Table 1.

[0135] (3) Thermal runaway test:

[0136] The batteries obtained in each embodiment and each comparative example were charged to 100% SOC, then overcharged with 1C current to trigger thermal runaway, charging was stopped, and after observing for 1 hour, the temperature of the large surface (shell surface) of the battery was tested. The results are shown in Table 1.

[0137] 2. Experimental results

[0138] The relevant electrochemical performance test results of the batteries obtained in the above embodiments and comparative examples are shown in Table 1.

[0139] Table 1 Test results of electrochemical performance of batteries obtained from the above embodiments and comparative examples

[0140]

[0141]

[0142] It can be seen from Table 1 that the battery prepared using the positive electrode sheet provided by the present invention has a lower DICR growth rate and a higher cycle capacity retention rate after a certain number of cycles. More importantly, the battery has good thermal stability and a low thermal runaway temperature. Please refer to Examples 1 to 11 for details.

[0143] In Comparative Example 1, the surface density difference between the first and second positive electrode active material layers is 9 g / m 2 , the surface density difference is too large, and the electron and ion transmission efficiency cannot reach a good balance, resulting in an increase in the DICR growth rate, a decrease in the cycle retention rate, and an increase in the thermal runaway temperature.

[0144] In Comparative Example 2, the surface densities of the first positive electrode active coating layer and the second positive electrode active material layer are both too small, the battery energy density decreases, and the battery DICR growth rate, cycle retention rate and thermal runaway temperature are also affected.

[0145] In Comparative Example 3, both the first and second positive electrode active material layers are coated with LMFP mixed with NCM positive electrode slurry, that is, the active materials of the first positive electrode active coating and the second positive electrode active coating are both LMFP+NCM. The combination of the two layers of active materials is poor, resulting in a decrease in ion and electron transport performance during the cycle process, resulting in an increase in the battery DICR growth rate, a decrease in the cycle retention rate, and an increase in the thermal runaway temperature.

[0146] In Comparative Example 4, the first layer (the side close to the aluminum foil) is coated with LMFP positive electrode slurry, and the second layer (the side away from the aluminum foil) is coated with NCM positive electrode slurry, that is, the active material layers of the first and second positive electrode active material layers are LMFP and NCM, respectively. Similar to Comparative Example 3, such a combination will lead to a decrease in ion and electron transport performance during the cycle process, resulting in an increase in the battery DICR growth rate, a decrease in the cycle retention rate, and an increase in the thermal runaway temperature.

[0147] In the first positive electrode active coating of Comparative Examples 5 and 6, the proportion of LMFP is respectively too large and too small, which will lead to a decrease in battery energy density or a decrease in thermal stability, thereby affecting the performance of the battery.

[0148] Further comparison of Example 1 with Examples 2 to 3 shows that when the surface density difference between the first and second positive electrode active material layers is not higher than 7 g / m 2, the battery prepared with the positive electrode sheet has good cycle performance and thermal stability, and the DICR growth rate is also low. It can also be seen that when the surface density difference between the first and second positive electrode active material layers is 0 (the surface density of the first and second positive electrode active material layers is equal, and in actual situations, the surface density difference between the two is adjusted to be very small, close to 0 or equal to 0), the performance of the battery in all aspects will be better, and the battery has better comprehensive performance.

[0149] Comparing Example 1 with Examples 4 to 5, compared with Example 1, the surface densities in Examples 4 and 5 are relatively smaller and larger, respectively. This will also affect the battery-related performance in Examples 4 and 5 to a certain extent. This is because too small a surface density will affect the battery energy density, while too large a surface density will affect the transmission performance of lithium ions and electrons.

[0150] Comparing Example 1 with Examples 6 to 8, compared with Example 1, the thickness d1 of the first positive electrode active coating in Example 6 is too small, and the difference in thickness between the first and second positive electrode active coatings is large, resulting in the lithium ion transmission or electron transmission performance being affected during the battery cycle, and the battery performance is reduced. In Example 8, the thickness d1 of the first positive electrode active coating and the thickness d2 of the first positive electrode active coating are both too small, and the total thickness of the positive electrode sheet is too small, the battery energy density is reduced, and the battery cycle effect and other performance will also be affected to a certain extent. In Example 9, the thickness d1 of the first positive electrode active coating and the thickness d2 of the first positive electrode active coating are both too large, and the total thickness of the positive electrode sheet is too large, the lithium ion transmission or electron transmission path is long, and it will also affect the overall battery cycle performance, resistance, thermal stability, etc.

[0151] Comparing Example 1 with Examples 9 to 11, compared with Example 1, the surface density of the negative electrode sheet in Example 9 is too large, the surface density of the negative electrode sheet in Example 10 is too small, and the thickness of the negative electrode sheet in Example 11 is too small, which will cause a decrease in the battery cycle performance. This shows that it is necessary to control the surface density and thickness of the negative electrode sheet to be more compatible with the positive electrode sheet and jointly optimize the battery-related performance.

[0152] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A positive electrode sheet, characterized in that: It includes a positive electrode current collector and a first positive electrode active coating and a second positive electrode active coating sequentially arranged on at least one side of the positive electrode current collector; The first positive electrode active coating is close to one side of the positive electrode current collector, and the first positive electrode active coating includes a first lithium iron manganese phosphate active material and a nickel-cobalt-manganese ternary active material; in the first positive electrode active coating, the mass proportion of the first lithium iron manganese phosphate active material is 82-88%, and the mass proportion of the nickel-cobalt-manganese ternary active material is 7-15%; The second positive electrode active coating is away from the positive electrode current collector, and the second positive electrode active coating includes a second lithium manganese iron phosphate active material; The surface density ρ1 of the first positive electrode active coating and the surface density ρ2 of the second positive electrode active coating satisfy: ρ1≥240g / m 2 , ρ2≥240g / m 2 ; and |ρ1-ρ2|≤7g / m 2 .

2. The positive electrode sheet according to claim 1, characterized in that: ρ1 and ρ2 satisfy: ρ1=ρ2.

3. The positive electrode sheet according to claim 1, characterized in that: ρ1, ρ2 meet: 240g / m 2 ≤ρ1≤260g / m 2 , 240g / m 2 ≤ρ2≤260g / m 2 .

4. The positive electrode sheet according to claim 1, characterized in that: The thickness d1 of the first positive electrode active coating layer and the thickness d2 of the second positive electrode active coating layer satisfy: d1≥105 μm, d2≥105 μm, and |d1-d2|≤3 μm.

5. The positive electrode sheet according to claim 1, characterized in that: The thickness D of the positive electrode sheet is ≥220 μm.

6. The positive electrode sheet according to claim 5, characterized in that: The thickness D of the positive electrode sheet satisfies: 220 μm≤D≤230 μm.

7. A method for preparing a positive electrode sheet according to any one of claims 1 to 6, characterized in that: The steps include: S1. Using the second lithium iron manganese phosphate active material, the second conductive agent, and the second binder to prepare a lithium iron manganese phosphate positive electrode slurry; using the first slurry, the nickel-cobalt-manganese ternary active material, the first conductive agent, and the first binder to prepare a lithium iron manganese phosphate mixed with nickel-cobalt-manganese ternary positive electrode slurry; S2. Control the viscosity difference between the lithium iron manganese phosphate positive electrode slurry and the lithium iron manganese phosphate mixed with nickel cobalt manganese ternary positive electrode slurry to be no more than 4000 mPa·s, and simultaneously apply the lithium iron manganese phosphate positive electrode slurry and the lithium iron manganese phosphate mixed with nickel cobalt manganese ternary positive electrode slurry on the positive electrode current collector, and dry to obtain the positive electrode sheet; The lithium manganese iron phosphate mixed with nickel, cobalt and manganese ternary positive electrode slurry is coated on the side close to the positive electrode current collector, and the lithium manganese iron phosphate positive electrode slurry is coated on the side away from the positive electrode current collector.

8. The method for preparing the positive electrode sheet according to claim 7, characterized in that: In S1 or S2, the viscosity of the lithium iron manganese phosphate positive electrode slurry is controlled to be 8000-16000 mPa·s, and the viscosity of the lithium iron manganese phosphate mixed with nickel, cobalt and manganese ternary positive electrode slurry is controlled to be 8000-16000 mPa·s.

9. A battery, characterized in that: It comprises the positive electrode sheet as claimed in any one of claims 1 to 6.

10. The battery according to claim 9, characterized in that: Also includes a negative electrode sheet, the surface density of the negative electrode sheet is 100 to 105 g / m 2 ; The thickness of the negative electrode sheet is 127-135 μm.

Citation Information

Patent Citations

  • Positive pole piece as well as preparation method and application thereof

    CN115692598A

  • Lithium ion battery, preparation method thereof and power vehicle

    CN116314636A

  • Lithium ion battery, preparation method thereof and power vehicle

    CN116315032A

  • Battery and preparation method thereof

    CN116705978A

  • Electrode plate, secondary battery and terminal device

    WO2023185743A1

Cited By

  • Positive electrode active material, positive electrode slurry, positive plate, battery and vehicle

    CN119447227A

  • Positive pole piece, preparation method thereof and lithium ion battery

    CN120432495A

  • Positive plate, preparation method thereof and battery

    CN121922570A

  • Positive electrode sheet, method for manufacturing the same, and battery

    CN121922570B

  • Positive electrode sheet and preparation method therefor, and battery

    EP4769537A1